Comparison of mono and bifacial modules for building integration and electric vehicle charging: A case study in Sweden - Khan, Sanjay; Sudhakar, K.; Mohd Hazwan, Yusof (Elsevier Ltd, 2023)
Future energy systems have a major difficulty in ensuring a reliable supply of electricity without affecting the environment, and numerous innovative renewables-based solutions are being introduced to meet this issue. This paper proposes a building photovoltaic (PV) system design for residential and electric vehicle (EV) charging demand and evaluates the techno-economic and environmental performance of the system in Orebro, Sweden, as it aims to become net zero carbon economy by 2045. Literature review shows that, although many studies exist, most of them did not fully consider the techno-economic and environmental aspects of PV systems for residential and EV charging loads in the chosen location. Two different PV technologies monofacial and bifacial monocrystalline panel in three different roof slopes 15°,30° and 45° has been analyzed to find the optimized system that can meet a typical house's annual energy demand. Economic indicators such as cumulative cash flow, levelized cost of electricity (LCOE), payback period and cost of EV charging have been evaluated for the PV system without discount and with discount which affects the system's profitability. PVSyst software was used to simulate the system for energy generation. Results have shown that the bifacial PV system performed better in energy generation, which is approximately 10% higher than the monofacial panel. However, in terms of economics, Case 6, a bifacial PV system with a roof angle of 45°, shows the lowest payback period of 7.3 years. In contrast, monofacial PV system with roof slope of 30° showed LCOE of 0.8988 Swedish Krona per kilowatt hour (SEK/kWh), EV charging cost of 0.1471 Swedish Krona per kilometer (SEK/km). Environmental parameters such as greenhouse gases (GHG) reduction have been analyzed. Results showed that GHG savings due to EV was higher than PV plant as Sweden's grid emission factor is very low due to less dependency on fossil fuels. The significance of this study will enable us to understand the performance of PV systems in Swedish aspect and methods can be extended to other countries for meeting location-specific energy demand.